1993
DOI: 10.1128/cmr.6.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of food-borne and waterborne viral gastroenteritis

Abstract: Norwalk virus infection is the epidemiologic prototype for outbreaks of food-borne and waterborne gastroenteritis. Around the world, Norwalk virus and Norwalk-like viruses appear to be major causes of food-borne and waterborne illness. Assessment of the overall significance of viral agents to the epidemiology of food-borne and waterborne illness is hampered by the lack of surveillance throughout much of the world. In areas where food-borne and waterborne illness surveillance is conducted, outbreaks of viral ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
2
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(103 citation statements)
references
References 108 publications
2
96
2
3
Order By: Relevance
“…Hedberg and Osterholm [7] have proposed that having more cases with vomiting than fever in an outbreak could be used as a further epidemiological criterion for NLV outbreaks. In this outbreak 32 people suffered from vomiting and 19 had fever, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Hedberg and Osterholm [7] have proposed that having more cases with vomiting than fever in an outbreak could be used as a further epidemiological criterion for NLV outbreaks. In this outbreak 32 people suffered from vomiting and 19 had fever, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The infection may be occurring through contaminated water or food and person-to-person contacts [Hedberg and Osterholm, 1993;Koopmans et al, 2002;Marshall and Bruggink, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have suggested that Norwalk virus and Norwalk-like viruses are the major causes of both foodand waterborne illnesses worldwide (143). In fact, in Bennett et al's (84) analysis of infectious and parasitic diseases, Norwalk virus was the only viral agent included as transmissible by water.…”
Section: Viral Pathogensmentioning
confidence: 99%